Globalization and College Students’ Attitudes towards Learning English in an Indonesian Context - Suwartono, Tono (Tecno Scientifica Publisher, 2024)
Learners’ attitudes towards learning English as a global language have been widely discussed, yet little is known about this in Indonesia. This study aims to address this knowledge gap by exploring the responses of Indonesian university students to a survey on their attitudes toward learning English in the context of globalization. A total of 333 students volunteered to participate, representing diverse departments within a faculty at a university in Central Java Province, Indonesia. To collect data, we carefully adapted and designed a questionnaire, which was administered online using Google Forms. The collected data were analyzed using descriptive statistics. The analysis suggests that college learners and users of English in Indonesia hold a positive attitude towards learning the language. We also provide pedagogical implications.